The boy in the black suit - Reynolds, Jason (Atheneum Books for Young Readers, 2015)
Soon after his mother's death, Matt takes a job at a funeral home in his tough Brooklyn neighborhood and, while attending and assisting with funerals, begins to accept her death and his responsibilities as a man.